Multi-layer corrosion-resistant weather-resistant adhesive film for metal plate and application method thereof

Through the anti -corrosion weather adhesion of the multi -layer structure, combined with specific materials and phase -changing micro -capsules, the problem of insufficient metal plate protective membrane durability and adhesion in the existing technologies, and realized efficient anti -corrosion and weather resistance. Reduce the cost of process.

CN119350991APending Publication Date: 2025-01-24FOSHAN DUOBANG POLYMER MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411413519.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When faced with complex environmental conditions, the existing metal plate protective films have insufficient durability and adhesion, which are prone to peeling, cracking or corrosion penetration, and the process cost is high.

Method used

Anti-corrosion and weather-resistant adhesive film with multi-layer structure, including metal bonding layer, intermediate transition layer and outer layer, through PE-g-MA blend, ethylene, octene, propylene multi-component blend and ethylene-propylene rubber polypropylene A combination of resins, combined with phase change microcapsules and nanomaterials, improves bond strength and weather resistance.

Benefits of technology

The excellent anti -corrosion, weather resistance and good adhesion of the metal board, reducing the cost of process and extending the service life of the metal board.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a multi-layer corrosion-resistant weather-resistant adhesive film for a metal plate and an application method of the multi-layer corrosion-resistant weather-resistant adhesive film. The multi-layer corrosion-resistant weather-resistant adhesive film comprises a metal adhesive layer, a middle transition layer and an outer surface layer, the metal bonding layer comprises a PE (polyethylene)-g-MA (maleic anhydride) blend; the middle transition layer comprises a multi-component blend of ethylene, octylene and propylene; the outer surface layer comprises polyolefin resin prepared from ethylene propylene rubber and polypropylene. The prepared multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate has the effects of being convenient to operate and remarkably improving the anti-corrosion and weather-resistant performance of the metal plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of metal plate protective films, and more specifically, to a multi-layer anticorrosion and weather-resistant adhesive film for metal plates and an application method thereof. Background Art

[0002] In modern industry and construction, metal materials are widely used in various structural parts and equipment due to their excellent mechanical strength and processing performance. However, when metal materials are exposed to air, moisture, salt and other corrosive media for a long time, they are prone to corrosion and aging, which affects their service life and safety. Therefore, how to effectively protect the metal surface and extend its service life has become an important issue in the engineering field. Although traditional anti-corrosion technologies, such as coating treatment and electroplating, can provide a certain degree of protection, their durability and adhesion are often insufficient when facing complex environmental conditions, and they are prone to peeling, cracking or corrosion penetration. In addition, with the increasing requirements for energy conservation and environmental protection in the industrial field, the research and development of new anti-corrosion materials and processes is imminent.

[0003] The existing TPO waterproofing membrane composite steel plate has two methods: using butyl glue to stick the steel plate on the top layer, using epoxy glue to stick the steel plate on the bottom layer, and using TPO and film to pre-stick and then stick the steel plate, which wastes a lot of manpower and material costs. Summary of the invention

[0004] In view of the problems existing in the prior art, the present application provides a multi-layer anti-corrosion and weather-resistant adhesive film for metal plates and an application method thereof.

[0005] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0006] The metal bonding layer comprises a PE-g-MA blend; the intermediate transition layer comprises a multi-component blend of ethylene, octene and propylene; and the outer surface layer comprises a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0007] Furthermore, the thickness of the metal bonding layer accounts for 5% to 45% of the thickness of the bonding film layer.

[0008] Furthermore, the thickness of the intermediate transition layer accounts for 20% to 60% of the thickness of the adhesive film layer.

[0009] Furthermore, the thickness of the outer layer accounts for 20% to 60% of the thickness of the adhesive film layer.

[0010] The multi-layer anti-corrosion and weather-resistant adhesive film for metal plates of the present invention realizes corrosion protection, weather resistance and good adhesion to metal plates through multi-layer structural design and selection of specific materials. The adhesive film is composed of a metal adhesive layer, an intermediate transition layer and an outer surface layer. The combination of these three layers not only enhances the overall physical properties, but also ensures the close adhesion of the adhesive film to the metal plate.

[0011] First, the metal bonding layer is mainly composed of PE-g-MA blend. PE-g-MA is a polyethylene (PE) modified by grafting maleic anhydride (MA). It has good polarity and bonding properties and can form a strong chemical bond with the surface of the metal plate. This layer accounts for 5% to 45% of the thickness of the entire bonding film, which can effectively ensure the bonding strength between the bonding film and the metal substrate. As the key layer for metal bonding, its thickness design ensures good adhesion and stability in different environments.

[0012] Secondly, the intermediate transition layer is composed of a multi-component blend of ethylene, octene, propylene, etc. This type of polymer has good flexibility, tensile strength and chemical stability, and can play a connecting role, that is, it not only enhances the bonding with the metal bonding layer, but also provides good support and connection for the outer surface layer. In the bonding film, the thickness of the intermediate transition layer accounts for 20% to 60%, which enables the bonding film to withstand stress changes in the environment, such as temperature fluctuations and mechanical shocks, during long-term use. The multi-component blend characteristics of this layer of material determine its excellent weather resistance and UV resistance, further extending the service life of the metal plate.

[0013] Finally, the outer layer is a polyolefin resin made by blending ethylene propylene rubber (EPDM) and polypropylene (PP). EPDM has excellent ozone resistance, aging resistance and chemical corrosion resistance, while polypropylene provides good mechanical strength and impact resistance. This outer layer can not only effectively prevent the invasion of external corrosive media, but also resist aging problems caused by long-term exposure to sunlight and harsh weather conditions. The thickness of the outer layer is controlled between 20% and 60% of the thickness of the bonding film layer. This ratio ensures that the outer layer will not be too thick to affect the flexibility and ductility of the entire film while providing protection.

[0014] Furthermore, the metal bonding layer, the intermediate transition layer and the outer surface layer also include phase change microcapsules accounting for 0.5% to 3% of the total content of the components of the layer.

[0015] Furthermore, the phase change microcapsule uses paraffin as a core material and melamine resin as a wall material.

[0016] Furthermore, the metal bonding layer contains phase change microcapsules accounting for 1.2% to 1.6% of the total content of the components of the layer; the intermediate transition layer contains phase change microcapsules accounting for 0.5% to 0.8% of the total content of the components of the layer; and the outer layer contains phase change microcapsules accounting for 2.5% to 3% of the total content of the components of the layer.

[0017] The metal bonding layer, the intermediate transition layer and the outer layer all contain a certain amount of phase change microcapsules, and the proportion of these microcapsules varies according to the functional requirements of different levels. The core material of the phase change microcapsule is paraffin, and the wall material is melamine resin. Its function is to store and release heat through the phase change of the material, thereby adjusting the temperature distribution of the bonding film. The content of phase change microcapsules in the metal bonding layer and the outer layer is higher than that in the intermediate transition layer, which makes the direct bonding between the bonding layer and the metal more stable and firm. Metal is usually a good thermal conductor. When the ambient temperature changes sharply, the surface temperature of the metal plate changes rapidly. The high content of phase change microcapsules in the metal bonding layer (1.2% to 1.6%) can absorb and release heat more effectively, avoid the contraction or expansion of the bonding layer due to sudden temperature changes, thereby reducing thermal stress and maintaining the bonding strength between the metal plate and the film layer. This thermal regulation function can greatly reduce the occurrence of thermal fatigue of the material and extend the service life. The outer layer is the part directly exposed to the external environment, and is subjected to erosion by ultraviolet radiation, temperature fluctuations and external climate changes. The high content of phase change microcapsules in the outer layer (2.5% to 3%) can quickly absorb heat at high temperatures and release it at low temperatures, keeping the temperature of the outer layer relatively stable. This not only prevents the film from aging too quickly, but also effectively extends its weather resistance. The thermal management requirements of the intermediate transition layer are relatively low, so a small content of phase change microcapsules (0.5% to 0.8%) can meet the temperature control requirements. The main function of this layer is to serve as a connection and buffer layer, and it is less sensitive to thermal stress.

[0018] Secondly, the high content of phase change microcapsules allows the bonding layer to maintain appropriate flexibility when the external temperature changes, and will not become brittle or hardened due to temperature changes. This flexibility can help the film layer better fit the surface of the metal plate, especially when the metal plate is slightly deformed or vibrated, which helps to reduce delamination or cracking at the bonding interface. The high content of phase change microcapsules in the outer layer not only ensures weather resistance and thermal regulation capabilities, but also helps to enhance the impact resistance of the film layer. When the outside world is subjected to mechanical impact or friction, the outer layer can absorb part of the impact energy through its phase change material, reducing damage to the film layer caused by external forces. This plays an important role in preventing external damage and extending the life of the film layer.

[0019] In addition, when the bonding layer is hot-pressed and bonded to the metal surface, the cooling rate of the bonding layer will also vary due to the different contents of the phase change microcapsules, so that the intermediate transition layer cools faster than the metal bonding layer and the outer layer, so that the bonding film as a whole can form a more firm and stable bond with the metal surface, avoiding too fast cooling resulting in a loose bond between the metal bonding layer and the metal.

[0020] Furthermore, the preparation method of the phase change microcapsules comprises the following steps:

[0021] A1: Dissolve the formaldehyde solution and melamine in water, add 0.5% to 2% of nano-SiO2 and 0.3% to 1% of nano-magnetic ferroferric oxide based on the mass of melamine, and stir at a speed of 1000 r / min and a temperature of 70°C for 45 minutes under alkaline conditions of pH 8.5 to obtain a prepolymer solution;

[0022] A2: paraffin wax, NaOH solid, and styrene-maleic anhydride copolymer were dissolved in water, the pH was maintained at 4.5, and then the mixture was stirred and emulsified at a speed of 3000 r / min and a temperature of 70°C for 90 min, and then ultrasonically dispersed for 30 min after stirring to obtain a paraffin wax emulsion;

[0023] A3: Slowly drip the prepolymer solution into the stirring paraffin emulsion, maintain the pH at 4.5, stir for 180 minutes, adjust the pH of the system to 8.5 after the reaction, wash and filter with deionized water, and dry at 50°C for 48 hours to obtain phase change microcapsules.

[0024] Furthermore, in the preparation method of the phase change microcapsules added to the metal bonding layer, 1.5% to 2% of nano-SiO2 and 0.3 to 0.5% of nano-magnetic ferroferric oxide are added based on the mass of melamine; in the preparation method of the phase change microcapsules added to the intermediate transition layer, 1% to 1.5% of nano-SiO2 and 0.6 to 0.7% of nano-magnetic ferroferric oxide are added based on the mass of melamine; in the preparation method of the phase change microcapsules added to the outer layer, 0.5% to 1% of nano-SiO2 and 0.8 to 1% of nano-magnetic ferroferric oxide are added based on the mass of melamine.

[0025] In the metal bonding layer, a higher proportion of nano-silicon dioxide (1.5% to 2%) and a moderate amount of nano-magnetic ferroferric oxide (0.3% to 0.5%) can enhance the mechanical strength and bonding performance of the bonding layer. Nano-SiO2 has excellent hardness and stability, which can improve the wear resistance and corrosion resistance of the bonding layer and ensure that it maintains bonding strength during long-term use. The appropriate amount of nano-Fe3O4 can produce a synergistic effect with the external magnetic field during the bonding process through its magnetism, thereby enhancing the adhesion of the metal surface. Such a proportional design ensures the structural stability of the bonding layer in a complex environment. The content of nano-SiO2 in the intermediate transition layer is slightly lower (1% to 1.5%), while the content of nano-Fe3O4 is relatively high (0.6% to 0.7%). This combination can ensure that the transition layer has sufficient flexibility while providing good bonding. Nano-SiO2 enhances the strength of the material, but due to its relatively low content, the material still maintains good flexibility and will not cause brittle fracture due to excessive rigidity. A higher content of nano-Fe3O4 can help maintain the stability of the layers during the bonding process by enhancing the magnetic effect, avoiding stress concentration, thereby better dispersing external forces and extending the service life of the adhesive film. The nano-SiO2 content in the outer layer is the lowest (0.5% to 1%), while the nano-Fe3O4 content is the highest (0.8% to 1%). This design helps to improve the weather resistance and aging resistance of the outer layer. The lower nano-SiO2 content ensures that the outer layer has moderate flexibility to avoid cracking or brittle cracking due to excessive hardening. The higher nano-Fe3O4 content can enhance the durability of the outer layer through its magnetic and thermal stability in the external environment changes (such as temperature fluctuations, ultraviolet radiation, etc.), especially when a magnetic field is applied, which can further enhance the anti-aging ability of the outer layer.

[0026] The invention discloses an application method of a multi-layer anti-corrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anti-corrosion and weather-resistant adhesive film is bonded to the metal plate by means of hot pressing and applying a magnetic field to one side of the metal plate.

[0027] In summary, the present invention has the following beneficial effects:

[0028] The multi-layer anti-corrosion and weather-resistant adhesive film for metal plates achieves excellent anti-corrosion, weather resistance and bonding properties through a carefully designed multi-layer structure and material combination. The film consists of a metal bonding layer, an intermediate transition layer and an outer layer. The material and thickness of each layer are designed to meet different functional requirements. The metal bonding layer uses a PE-g-MA blend, which uses the polarity of maleic anhydride grafted polyethylene to enhance adhesion and form a strong chemical bond with the metal. Its thickness ratio is 5% to 45%, ensuring strong adhesion between the bonding film and the metal substrate. The intermediate transition layer improves flexibility and tensile strength through a blend of ethylene, octene and propylene, ensuring the stability of the bonding film under temperature fluctuations and mechanical stress. The outer layer uses polyolefin resin to further enhance the weather resistance and anti-aging ability of the film. In addition, by regulating the phase change microcapsules in the three layers and the ratio of nano-silicon dioxide and nano-ferroferric oxide in the phase change microcapsules, the wear resistance, corrosion resistance and adhesion of the material are greatly improved. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] Example 1

[0031] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0032] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0033] The thickness of the metal bonding layer accounts for 5% of the thickness of the bonding film layer.

[0034] The thickness of the intermediate transition layer accounts for 60% of the thickness of the bonding film layer.

[0035] The thickness of the outer layer accounts for 35% of the thickness of the bonding film layer.

[0036] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0037] The invention discloses an application method of a multi-layer anticorrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anticorrosion and weather-resistant adhesive film is hot-pressed onto the surface of the metal plate by hot-pressing.

[0038] Example 2

[0039] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0040] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0041] The thickness of the metal bonding layer accounts for 45% of the thickness of the bonding film layer.

[0042] The thickness of the intermediate transition layer accounts for 30% of the thickness of the bonding film layer.

[0043] The thickness of the outer layer accounts for 25% of the thickness of the bonding film layer.

[0044] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0045] The invention discloses an application method of a multi-layer anticorrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anticorrosion and weather-resistant adhesive film is hot-pressed onto the surface of the metal plate by hot-pressing.

[0046] Example 3

[0047] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0048] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0049] The thickness of the metal bonding layer accounts for 25% of the thickness of the bonding film layer.

[0050] The thickness of the intermediate transition layer accounts for 40% of the thickness of the bonding film layer.

[0051] The thickness of the outer layer accounts for 35% of the thickness of the bonding film layer.

[0052] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0053] The invention discloses an application method of a multi-layer anticorrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anticorrosion and weather-resistant adhesive film is hot-pressed onto the surface of the metal plate by hot-pressing.

[0054] Example 4

[0055] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0056] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0057] The thickness of the metal bonding layer accounts for 25% of the thickness of the bonding film layer.

[0058] The thickness of the intermediate transition layer accounts for 40% of the thickness of the bonding film layer.

[0059] The thickness of the outer layer accounts for 35% of the thickness of the bonding film layer.

[0060] The metal bonding layer, the intermediate transition layer and the outer surface layer also include phase change microcapsules accounting for 2% of the total content of the components of the layer. The phase change microcapsules use paraffin as the core material and melamine resin as the wall material.

[0061] The preparation method of phase change microcapsules comprises the following steps:

[0062] A1: 8 ml of formaldehyde solution and 3 g of melamine were dissolved in water, and stirred at 1000 r / min and 70°C for 45 min under alkaline conditions with a pH of 8.5 to obtain a prepolymer solution;

[0063] A2: paraffin wax, NaOH solid, and styrene-maleic anhydride copolymer were dissolved in water, the pH was maintained at 4.5, and then the mixture was stirred and emulsified at a speed of 3000 r / min and a temperature of 70°C for 90 min, and then ultrasonically dispersed for 30 min after stirring to obtain a paraffin wax emulsion;

[0064] A3: Slowly drip the prepolymer solution into the stirring paraffin emulsion, maintain the pH at 4.5, stir for 180 minutes, adjust the pH of the system to 8.5 after the reaction, wash and filter with deionized water, and dry at 50°C for 48 hours to obtain phase change microcapsules.

[0065] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0066] The invention discloses an application method of a multi-layer anticorrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anticorrosion and weather-resistant adhesive film is hot-pressed onto the surface of the metal plate by hot-pressing.

[0067] Example 5

[0068] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0069] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0070] The thickness of the metal bonding layer accounts for 25% of the thickness of the bonding film layer.

[0071] The thickness of the intermediate transition layer accounts for 40% of the thickness of the bonding film layer.

[0072] The thickness of the outer layer accounts for 35% of the thickness of the bonding film layer.

[0073] The metal bonding layer, the intermediate transition layer and the outer surface layer also include phase change microcapsules accounting for 3% of the total content of the components of the layer. The phase change microcapsules use paraffin as the core material and melamine resin as the wall material.

[0074] The preparation method of phase change microcapsules comprises the following steps:

[0075] A1: 8 ml of formaldehyde solution and 3 g of melamine were dissolved in water, and stirred at 1000 r / min and 70°C for 45 min under alkaline conditions with a pH of 8.5 to obtain a prepolymer solution;

[0076] A2: paraffin wax, NaOH solid, and styrene-maleic anhydride copolymer were dissolved in water, the pH was maintained at 4.5, and then the mixture was stirred and emulsified at a speed of 3000 r / min and a temperature of 70°C for 90 min, and then ultrasonically dispersed for 30 min after stirring to obtain a paraffin wax emulsion;

[0077] A3: Slowly drip the prepolymer solution into the stirring paraffin emulsion, maintain the pH at 4.5, stir for 180 minutes, adjust the pH of the system to 8.5 after the reaction, wash and filter with deionized water, and dry at 50°C for 48 hours to obtain phase change microcapsules.

[0078] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0079] The invention discloses an application method of a multi-layer anticorrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anticorrosion and weather-resistant adhesive film is hot-pressed onto the surface of the metal plate by hot-pressing.

[0080] Example 6

[0081] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0082] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0083] The thickness of the metal bonding layer accounts for 25% of the thickness of the bonding film layer.

[0084] The thickness of the intermediate transition layer accounts for 40% of the thickness of the bonding film layer.

[0085] The thickness of the outer layer accounts for 35% of the thickness of the bonding film layer.

[0086] The metal bonding layer, the intermediate transition layer and the outer surface layer also include phase change microcapsules accounting for 0.5% of the total content of the components of the layer. The phase change microcapsules use paraffin as the core material and melamine resin as the wall material.

[0087] The preparation method of phase change microcapsules comprises the following steps:

[0088] A1: 8 ml of formaldehyde solution and 3 g of melamine were dissolved in water, and stirred at 1000 r / min and 70°C for 45 min under alkaline conditions with a pH of 8.5 to obtain a prepolymer solution;

[0089] A2: paraffin wax, NaOH solid, and styrene-maleic anhydride copolymer were dissolved in water, the pH was maintained at 4.5, and then the mixture was stirred and emulsified at a speed of 3000 r / min and a temperature of 70°C for 90 min, and then ultrasonically dispersed for 30 min after stirring to obtain a paraffin wax emulsion;

[0090] A3: Slowly drip the prepolymer solution into the stirring paraffin emulsion, maintain the pH at 4.5, stir for 180 minutes, adjust the pH of the system to 8.5 after the reaction, wash and filter with deionized water, and dry at 50°C for 48 hours to obtain phase change microcapsules.

[0091] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0092] The invention discloses an application method of a multi-layer anticorrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anticorrosion and weather-resistant adhesive film is hot-pressed onto the surface of the metal plate by hot-pressing.

[0093] Example 7

[0094] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0095] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0096] The thickness of the metal bonding layer accounts for 25% of the thickness of the bonding film layer.

[0097] The thickness of the intermediate transition layer accounts for 40% of the thickness of the bonding film layer.

[0098] The thickness of the outer layer accounts for 35% of the thickness of the bonding film layer.

[0099] The metal bonding layer contains 1.2% of the total content of the phase change microcapsules in the layer; the intermediate transition layer contains 0.5% of the total content of the phase change microcapsules in the layer; the outer layer contains 2.5% of the total content of the phase change microcapsules in the layer. The phase change microcapsules use paraffin as the core material and melamine resin as the wall material.

[0100] The preparation method of phase change microcapsules comprises the following steps:

[0101] A1: 8 ml of formaldehyde solution and 3 g of melamine were dissolved in water, and stirred at 1000 r / min and 70°C for 45 min under alkaline conditions with a pH of 8.5 to obtain a prepolymer solution;

[0102] A2: paraffin wax, NaOH solid, and styrene-maleic anhydride copolymer were dissolved in water, the pH was maintained at 4.5, and then the mixture was stirred and emulsified at a speed of 3000 r / min and a temperature of 70°C for 90 min, and then ultrasonically dispersed for 30 min after stirring to obtain a paraffin wax emulsion;

[0103] A3: Slowly drip the prepolymer solution into the stirring paraffin emulsion, maintain the pH at 4.5, stir for 180 minutes, adjust the pH of the system to 8.5 after the reaction, wash and filter with deionized water, and dry at 50°C for 48 hours to obtain phase change microcapsules.

[0104] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0105] The invention discloses an application method of a multi-layer anticorrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anticorrosion and weather-resistant adhesive film is hot-pressed onto the surface of the metal plate by hot-pressing.

[0106] Example 8

[0107] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0108] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0109] The thickness of the metal bonding layer accounts for 25% of the thickness of the bonding film layer.

[0110] The thickness of the intermediate transition layer accounts for 40% of the thickness of the bonding film layer.

[0111] The thickness of the outer layer accounts for 35% of the thickness of the bonding film layer.

[0112] The metal bonding layer contains 1.6% of the total content of the phase change microcapsules in the layer; the intermediate transition layer contains 0.8% of the total content of the phase change microcapsules in the layer; the outer layer contains 3% of the total content of the phase change microcapsules in the layer. The phase change microcapsules use paraffin as the core material and melamine resin as the wall material.

[0113] The preparation method of phase change microcapsules comprises the following steps:

[0114] A1: 8 ml of formaldehyde solution and 3 g of melamine were dissolved in water, and stirred at 1000 r / min and 70°C for 45 min under alkaline conditions with a pH of 8.5 to obtain a prepolymer solution;

[0115] A2: paraffin wax, NaOH solid, and styrene-maleic anhydride copolymer were dissolved in water, the pH was maintained at 4.5, and then the mixture was stirred and emulsified at a speed of 3000 r / min and a temperature of 70°C for 90 min, and then ultrasonically dispersed for 30 min after stirring to obtain a paraffin wax emulsion;

[0116] A3: Slowly drip the prepolymer solution into the stirring paraffin emulsion, maintain the pH at 4.5, stir for 180 minutes, adjust the pH of the system to 8.5 after the reaction, wash and filter with deionized water, and dry at 50°C for 48 hours to obtain phase change microcapsules.

[0117] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0118] The invention discloses an application method of a multi-layer anticorrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anticorrosion and weather-resistant adhesive film is hot-pressed onto the surface of the metal plate by hot-pressing.

[0119] Example 9

[0120] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0121] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0122] The thickness of the metal bonding layer accounts for 25% of the thickness of the bonding film layer.

[0123] The thickness of the intermediate transition layer accounts for 40% of the thickness of the bonding film layer.

[0124] The thickness of the outer layer accounts for 35% of the thickness of the bonding film layer.

[0125] The metal bonding layer contains 1.4% of the total content of the phase change microcapsules in the layer; the intermediate transition layer contains 0.6% of the total content of the phase change microcapsules in the layer; the outer layer contains 2.7% of the total content of the phase change microcapsules in the layer. The phase change microcapsules use paraffin as the core material and melamine resin as the wall material.

[0126] The preparation method of phase change microcapsules comprises the following steps:

[0127] A1: 8 ml of formaldehyde solution and 3 g of melamine were dissolved in water, and stirred at 1000 r / min and 70°C for 45 min under alkaline conditions with a pH of 8.5 to obtain a prepolymer solution;

[0128] A2: paraffin wax, NaOH solid, and styrene-maleic anhydride copolymer were dissolved in water, the pH was maintained at 4.5, and then the mixture was stirred and emulsified at a speed of 3000 r / min and a temperature of 70°C for 90 min, and then ultrasonically dispersed for 30 min after stirring to obtain a paraffin wax emulsion;

[0129] A3: Slowly drip the prepolymer solution into the stirring paraffin emulsion, maintain the pH at 4.5, stir for 180 minutes, adjust the pH of the system to 8.5 after the reaction, wash and filter with deionized water, and dry at 50°C for 48 hours to obtain phase change microcapsules.

[0130] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0131] The invention discloses an application method of a multi-layer anticorrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anticorrosion and weather-resistant adhesive film is hot-pressed onto the surface of the metal plate by hot-pressing.

[0132] Example 10

[0133] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0134] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0135] The thickness of the metal bonding layer accounts for 25% of the thickness of the bonding film layer.

[0136] The thickness of the intermediate transition layer accounts for 40% of the thickness of the bonding film layer.

[0137] The thickness of the outer layer accounts for 35% of the thickness of the bonding film layer.

[0138] The metal bonding layer contains phase change microcapsules accounting for 1.4% of the total content of the components of the layer; the intermediate transition layer contains phase change microcapsules accounting for 0.6% of the total content of the components of the layer; and the outer layer contains phase change microcapsules accounting for 2.7% of the total content of the components of the layer.

[0139] Phase change microcapsules use paraffin as the core material and melamine resin as the wall material.

[0140] The preparation method of phase change microcapsules comprises the following steps:

[0141] A1: Dissolve the formaldehyde solution and melamine in water, and add 0.5% to 2% of nano-SiO2 and 0.3% to 1% of nano-magnetic ferroferric oxide based on the mass of melamine (wherein, in the preparation method of the phase-change microcapsules added to the metal bonding layer, 1.5% of nano-SiO2 and 0.3% of nano-magnetic ferroferric oxide based on the mass of melamine are added; in the preparation method of the phase-change microcapsules added to the intermediate transition layer, 1% of nano-SiO2 and 0.6% of nano-magnetic ferroferric oxide based on the mass of melamine are added; in the preparation method of the phase-change microcapsules added to the outer layer, 0.5% of nano-SiO2 and 0.8% of nano-magnetic ferroferric oxide based on the mass of melamine are added). Stir for 45 minutes at a speed of 1000 r / min and a temperature of 70° C. under alkaline conditions with a pH of 8.5 to obtain a prepolymer solution;

[0142] A2: paraffin wax, NaOH solid, and styrene-maleic anhydride copolymer were dissolved in water, the pH was maintained at 4.5, and then the mixture was stirred and emulsified at a speed of 3000 r / min and a temperature of 70°C for 90 min, and then ultrasonically dispersed for 30 min after stirring to obtain a paraffin wax emulsion;

[0143] A3: Slowly drip the prepolymer solution into the stirring paraffin emulsion, maintain the pH at 4.5, stir for 180 minutes, adjust the pH of the system to 8.5 after the reaction, wash and filter with deionized water, and dry at 50°C for 48 hours to obtain phase change microcapsules.

[0144] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0145] The invention discloses an application method of a multi-layer anti-corrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anti-corrosion and weather-resistant adhesive film is bonded to the metal plate by means of hot pressing and applying a magnetic field to one side of the metal plate.

[0146] Embodiment 11

[0147] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0148] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0149] The thickness of the metal bonding layer accounts for 25% of the thickness of the bonding film layer.

[0150] The thickness of the intermediate transition layer accounts for 40% of the thickness of the bonding film layer.

[0151] The thickness of the outer layer accounts for 35% of the thickness of the bonding film layer.

[0152] The metal bonding layer contains phase change microcapsules accounting for 1.4% of the total content of the components of the layer; the intermediate transition layer contains phase change microcapsules accounting for 0.6% of the total content of the components of the layer; and the outer layer contains phase change microcapsules accounting for 2.7% of the total content of the components of the layer.

[0153] Phase change microcapsules use paraffin as the core material and melamine resin as the wall material.

[0154] The preparation method of phase change microcapsules comprises the following steps:

[0155] A1: Dissolve the formaldehyde solution and melamine in water, and add 0.5% to 2% of nano-SiO2 and 0.3 to 1% of nano-magnetic ferroferric oxide based on the mass of melamine (wherein, in the preparation method of the phase-change microcapsules added to the metal bonding layer, 2% of the mass of melamine and 0.5% of the nano-magnetic ferroferric oxide are added; in the preparation method of the phase-change microcapsules added to the intermediate transition layer, 1.5% of the mass of melamine and 0.7% of the nano-magnetic ferroferric oxide are added; in the preparation method of the phase-change microcapsules added to the outer layer, 1% of the mass of melamine and 1% of the nano-SiO2 are added.) Maintain an alkaline condition of pH 8.5, stir at a speed of 1000 r / min and a temperature of 70°C for 45 minutes to obtain a prepolymer solution;

[0156] A2: paraffin wax, NaOH solid, and styrene-maleic anhydride copolymer were dissolved in water, the pH was maintained at 4.5, and then the mixture was stirred and emulsified at a speed of 3000 r / min and a temperature of 70°C for 90 min, and then ultrasonically dispersed for 30 min after stirring to obtain a paraffin wax emulsion;

[0157] A3: Slowly drip the prepolymer solution into the stirring paraffin emulsion, maintain the pH at 4.5, stir for 180 minutes, adjust the pH of the system to 8.5 after the reaction, wash and filter with deionized water, and dry at 50°C for 48 hours to obtain phase change microcapsules.

[0158] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0159] The invention discloses an application method of a multi-layer anti-corrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anti-corrosion and weather-resistant adhesive film is bonded to the metal plate by means of hot pressing and applying a magnetic field to one side of the metal plate.

[0160] Example 12

[0161] A multi-layer anti-corrosion and weather-resistant adhesive film for metal plates, comprising a metal adhesive layer for bonding with the metal plate, an intermediate transition layer and an outer surface layer;

[0162] The metal bonding layer includes a PE-g-MA blend; the intermediate transition layer includes a multi-component blend of ethylene, octene and propylene; and the outer surface layer includes a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

[0163] The thickness of the metal bonding layer accounts for 25% of the thickness of the bonding film layer.

[0164] The thickness of the intermediate transition layer accounts for 40% of the thickness of the bonding film layer.

[0165] The thickness of the outer layer accounts for 35% of the thickness of the bonding film layer.

[0166] The metal bonding layer contains phase change microcapsules accounting for 1.4% of the total content of the components of the layer; the intermediate transition layer contains phase change microcapsules accounting for 0.6% of the total content of the components of the layer; and the outer layer contains phase change microcapsules accounting for 2.7% of the total content of the components of the layer.

[0167] Phase change microcapsules use paraffin as the core material and melamine resin as the wall material.

[0168] The preparation method of phase change microcapsules comprises the following steps:

[0169] A1: Dissolve the formaldehyde solution and melamine in water, and add 0.5% to 2% of nano-SiO2 and 0.3 to 1% of nano-magnetic ferroferric oxide based on the mass of melamine (wherein, in the preparation method of the phase-change microcapsules added to the metal bonding layer, 1.7% of nano-SiO2 and 0.4% of nano-magnetic ferroferric oxide are added; in the preparation method of the phase-change microcapsules added to the intermediate transition layer, 1.3% of nano-SiO2 and 0.7% of nano-magnetic ferroferric oxide are added; in the preparation method of the phase-change microcapsules added to the outer layer, 0.7% of nano-SiO2 and 0.9% of nano-magnetic ferroferric oxide are added.) Maintaining an alkaline condition of pH 8.5, stirring at a speed of 1000 r / min and a temperature of 70°C for 45 minutes, a prepolymer solution is obtained;

[0170] A2: paraffin wax, NaOH solid, and styrene-maleic anhydride copolymer were dissolved in water, the pH was maintained at 4.5, and then the mixture was stirred and emulsified at a speed of 3000 r / min and a temperature of 70°C for 90 min, and then ultrasonically dispersed for 30 min after stirring to obtain a paraffin wax emulsion;

[0171] A3: Slowly drip the prepolymer solution into the stirring paraffin emulsion, maintain the pH at 4.5, stir for 180 minutes, adjust the pH of the system to 8.5 after the reaction, wash and filter with deionized water, and dry at 50°C for 48 hours to obtain phase change microcapsules.

[0172] The multi-layer anti-corrosion and weather-resistant adhesive film for the metal plate is prepared by a multi-layer co-extrusion method.

[0173] The invention discloses an application method of a multi-layer anti-corrosion and weather-resistant adhesive film for a metal plate, wherein the multi-layer anti-corrosion and weather-resistant adhesive film is bonded to the metal plate by means of hot pressing and applying a magnetic field to one side of the metal plate.

[0174] Comparative Example

[0175] In Comparative Example 1, epoxy glue was used to bond the TPO layer to the surface of the metal plate.

[0176] Detection Methods

[0177] The adhesive films of Examples 1-12 were bonded to the steel plate, and the TPO layer of Comparative Example 1 was bonded to the surface of the steel plate with epoxy glue to obtain Example and Comparative Example samples. Subsequently, a xenon lamp aging test for 10,000 hours was performed, and the same batch of Example and Comparative Example samples were first exposed to outdoor sunlight for 6 months and then subjected to a xenon lamp aging test for 60,000 hours. The test results are shown in Table 1 below.

[0178] Table 1

[0179]

[0180] The above test results show that the adhesive film of the present invention is easy to construct and has good weather resistance. The weather resistance of the adhesive film is significantly improved after adding phase change microcapsules and doping nano silicon dioxide and nano magnetic ferroferric oxide into the wall material of the phase change microcapsules.

[0181] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A multi-layer anticorrosion and weather-resistant adhesive film for metal plates, characterized in that: It includes a metal bonding layer for bonding with a metal plate, an intermediate transition layer and an outer surface layer; The metal bonding layer comprises a PE-g-MA blend; the intermediate transition layer comprises a multi-component blend of ethylene, octene and propylene; and the outer surface layer comprises a polyolefin resin prepared from ethylene-propylene rubber and polypropylene.

2. The multi-layer anticorrosion and weather-resistant adhesive film for metal plates according to claim 1, characterized in that: The thickness of the metal bonding layer accounts for 5% to 45% of the thickness of the bonding film layer.

3. The multi-layer anticorrosion and weather-resistant adhesive film for metal plates according to claim 2, characterized in that: The thickness of the intermediate transition layer accounts for 20% to 60% of the thickness of the adhesive film layer.

4. The multi-layer anticorrosion and weather-resistant adhesive film for metal plates according to claim 3, characterized in that: The thickness of the outer layer accounts for 20% to 60% of the thickness of the adhesive film layer.

5. The multi-layer anticorrosion and weather-resistant adhesive film for metal plates according to claim 1, characterized in that: The metal bonding layer, the intermediate transition layer and the outer surface layer also include phase change microcapsules accounting for 0.5% to 3% of the total content of the components of the layer.

6. The multi-layer anticorrosion and weather-resistant adhesive film for metal plates according to claim 5, characterized in that: The phase-change microcapsule uses paraffin as the core material and melamine resin as the wall material.

7. The multi-layer anticorrosion and weather-resistant adhesive film for metal plates according to claim 5, characterized in that: The metal bonding layer contains phase change microcapsules accounting for 1.2% to 1.6% of the total content of the components of the layer; the intermediate transition layer contains phase change microcapsules accounting for 0.5% to 0.8% of the total content of the components of the layer; and the outer layer contains phase change microcapsules accounting for 2.5% to 3% of the total content of the components of the layer.

8. The multi-layer anticorrosion and weather-resistant adhesive film for metal plates according to claim 1, characterized in that: The preparation method of the phase change microcapsule comprises the following steps: A1: Dissolve the formaldehyde solution and melamine in water, add 0.5% to 2% of nano-SiO2 and 0.3% to 1% of nano-magnetic ferroferric oxide based on the mass of melamine, and stir at a speed of 1000 r / min and a temperature of 70°C for 45 minutes under alkaline conditions of pH 8.5 to obtain a prepolymer solution; A2: paraffin wax, NaOH solid, and styrene-maleic anhydride copolymer were dissolved in water, the pH was maintained at 4.5, and then the mixture was stirred and emulsified at a speed of 3000 r / min and a temperature of 70°C for 90 min, and then ultrasonically dispersed for 30 min after stirring to obtain a paraffin wax emulsion; A3: Slowly drip the prepolymer solution into the stirring paraffin emulsion, maintain the pH at 4.5, stir for 180 minutes, adjust the pH of the system to 8.5 after the reaction, wash and filter with deionized water, and dry at 50°C for 48 hours to obtain phase change microcapsules.

9. The multi-layer anticorrosion and weather-resistant adhesive film for metal plates according to claim 1, characterized in that: In the preparation method of the phase change microcapsules added to the metal bonding layer, 1.5% to 2% of nano-SiO2 and 0.3 to 0.5% of nano-magnetic ferroferric oxide are added based on the mass of melamine; in the preparation method of the phase change microcapsules added to the intermediate transition layer, 1% to 1.5% of nano-SiO2 and 0.6 to 0.7% of nano-magnetic ferroferric oxide are added based on the mass of melamine; in the preparation method of the phase change microcapsules added to the outer layer, 0.5% to 1% of nano-SiO2 and 0.8 to 1% of nano-magnetic ferroferric oxide are added based on the mass of melamine.

10. A method for applying the multi-layer anticorrosion and weather-resistant adhesive film for metal plates according to any one of claims 1 to 9, characterized in that: The multi-layer anti-corrosion and weather-resistant adhesive film is bonded to the metal plate by means of heat pressing and applying a magnetic field to one side of the metal plate.